Dampak Kontrol Diri Remaja Penggemar K-POP Di Kabupaten Jember - Achtiar, Rina; Sanusi, Nurul Izza Anwar; Fitriana, Aniqotuzzuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
K-pop has become a global phenomenon in recent years, with a wide following around the world. However, the popularity of K-pop has raised some concerns about its impact on adolescent self-control. This study aims to evaluate the impact of k-pop fans' adolescent self-control in Jember District. This study used a qualitative approach, specifically focusing on descriptive qualitative research methods using observation and interviews to collect and obtain data from young k-pop fans in Jember Regency. Respondents will be asked to answer a number of questions which will include the impact of the kpop world on teenagers, self-control behavior, the impact that affects adolescent self-control, and the relationship between management and self-control. The results of this study are expected to provide an overview of the impact of self-control among adolescent k-pop fans in Jember Regency. This can help the community and parents understand the impact of self-control on youth K-pop fans, so that it can increase efforts to develop appropriate educational and supervision programs to help adolescents develop good self-control.